PENERAPAN KAIDAH FIKIH MUAMALAH DALAM PRAKTIK EKONOMI GIG: ANALISIS TENTANG KEADILAN DAN KEABSAHAN AKAD DI ERA DIGITAL - Ira Zulfia Kausar; Abdul Helim; Syaikhu (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2026)
Abstrak This study discusses the Application of Mu'āmalāt Fiqh Principles in Gig Economy Practices: An Analysis of Fairness and Contract Validity in the Digital Age. There are two discussions: the first is the gig economy with the application of mu'amalat fiqh rules, and the second is the value of fairness in the gig economy as viewed from maqashid sharia. The explanation is carried out using a normative approach with a normative juridical method and a conceptual approach accompanied by a literature study of books and digital journals related to the gig economy, mashlahah, and maqashid sharia. The application of muamalah fiqh principles based on the Qur'an and hadith provides an understanding that the gig economy needs to be studied using Islamic business ethics, namely avoiding riba, gharar, tadlis, maysir, fasid, and batil, by harmonizing the values of maqashid syariah in its application in order to obtain a validity value that is in accordance with sharia. Keyword : fiqh principles, muamalah, gig economy